Facilitating Recovery through Building an Interconnected Community: From Awareness to Action - Ma, Kyunghee (Journal of International Students, 2021)
This article describes stress that many Asian international students experience during their adjustment to U.S. universities. Reflecting on personal experiences that contributed to deeper self-understanding, I explain cultural incompatibilities that cause this stress, the negative impact that the stress has on mental health, and the lack of support systems that exacerbate mental health complications. In highlighting the prioritization of the mental health in Asian international students and initiating community outreach programs, I demonstrate that when Asian international students participate in creating an interconnected community, they have the potential to thrive despite the stressful adjustment period.